1992
DOI: 10.1161/01.str.23.5.657
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of long-term outcome and safety after hemodilution therapy in acute ischemic stroke.

Abstract: In a previous single-center, randomized controlled trial including 102 patients treated in a stroke unit, we showed that rapid, modest hemodilution improved short-term clinical outcome in ischemic stroke patients. I now evaluate the long-term outcome and potential risks of this combined venesection/dextran 40 therapy in the same 52 treated and 50 control patients. Mortality, need for institutional care, and recurrent strokes were registered during 1 year following inclusion in the trial, and a final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 27 publications
1
19
0
5
Order By: Relevance
“…Studies investigating this issue have been discouraging. Both studies conducted by means of isovolemic hemodilution with dextran [105], and later studies of hypervolemic hemodilution by venipunction administration of pentastarch [106] were negative. In a meta-analysis of 18 control studies [107] it was demonstrated that this procedure did not significantly reduce mortality or the degree of incapacity.…”
Section: Control Of Arterial Oxygen Saturationmentioning
confidence: 99%
“…Studies investigating this issue have been discouraging. Both studies conducted by means of isovolemic hemodilution with dextran [105], and later studies of hypervolemic hemodilution by venipunction administration of pentastarch [106] were negative. In a meta-analysis of 18 control studies [107] it was demonstrated that this procedure did not significantly reduce mortality or the degree of incapacity.…”
Section: Control Of Arterial Oxygen Saturationmentioning
confidence: 99%
“…Several large clinical trials of isovolemic hemodilution failed to demonstrate a decline in mortality or disability with treatment [179][180][181] . Hypervolemic hemodilution was assessed in small randomized trials with conflicting results.…”
Section: Hemodilutionmentioning
confidence: 99%
“…The clinical benefit of haemodilution therapy has not been established, and the possibility of excess brain oedema has not been excluded [Strand et al, 1992; Italian Acute Stroke Study Group, 1988;Scandinavian Stroke Study Group, 1987; Hemodilution in Stroke Study Group, 1989]. …”
Section: Haemodilutionmentioning
confidence: 99%